EMOTIONAL INTELLIGENCE AND ANXIETY TOWARD NATIONAL FINAL EXAMINATION IN JUNIOR HIGH SCHOOL’S STUDENTS - Arsalan, Yaniz; Khairani, Maya; Sari, Kartika (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
National Final Examination is one of the tests that must be passed by each student in Indonesia who want to continue to pursue higher education. The test could cause anxiety on students due to graduation standards. One of the things that influence anxiety toward this test is individual characteristic especially the ability to regulate emotions which are very closely related to emotional intelligence. The sample of this study was 350 students in grade 3 junior high school that will facing National Final Examination from three schools in Banda Aceh. Data collected by The Emotional Intelligence Scale and The Anxiety Toward National Final Examination Scale. The results showed a correlation coefficient r = – 0.376, p = 0.000 ( P <0.05 ). This result implied that there is a negative correlation between emotional intelligence with anxiety toward National Final Examination in grade 3 junior high school’s students in Banda Aceh.Keywords: Emotional Intelligence, Anxiety, National Final Examination.